How to Improve Students’ Cognitive Ability?: The Influence of Two Stay Two Stray Type Cooperative Model Assisted by Innovative Module - Ramadhani, Farralia; Yetri, Yetri; Irwandani, Irwandani (Indonesian Journal of Science and Mathematics Education, 2021)
This study aims to see the effect of using the two stay two stray learning model assisted by an innovative module on the cognitive learning outcomes of students on the topic of simple machines. This quantitative study used a quasi-experimental design with a pretest-posttest control group design. This study consisted of 2 classes, class VIII A as the experimental class and class VIII B as the control class. The results showed that the average of the cognitive test of the experimental class was 80.00 and the control class was 72.67. The results of data processing using the Mann Whitney test with a sig level of 0.05 revealed that the results of sig.2 tailed were 0.000, less than 0.05, which means that there is a difference in the posttest average value of students’ cognitive learning outcomes in the control and experimental classes.